NORTHEASTERNERS IN BRUSQUE/SC: STIGMA AND PREJUDICE IN THE TRAJECTORY OF NEW MIGRANTS - Cassaniga, Tafarel (Seven Editora, 2026)
Since the mid-20th century, northeastern migratory flows toward South-Central Brazil have been a structural phenomenon of national demographic dynamics, with São Paulo as the historical destination. However, the beginning of the 21st century reveals a spatial redistribution of these flows, driving the northeastern presence into new frontiers, such as the state of Santa Catarina. This article analyzes the characteristics of this migration and its impacts on the daily life of host cities, taking the municipality of Brusque/SC as the object of study. The methodology was based on ethnographic research, utilizing interviews and life histories of both migrants and native residents. The results indicate that the insertion of northeasterners in Brusque is marked by sociocultural tensions and processes of stigmatization, manifested in the use of the label "baiano" as a category of inferiority. It is concluded that prejudice and racial discrimination operate as defense mechanisms for a local identity idealized around whiteness and the 19th-century Germanic heritage, invisibilizing the contribution of new migrants and hindering intercultural dialogue within the territory.DOI: https://doi.org/10.56238/sevened2026.001-008